PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP AKTIVITAS DAN HASIL BELAJAR IPS SISWA SDN 8 TANANTOVEA - Muznah, Muznah; Jamaludin, Jamaludin; Jennah, Ali (Katalogis, 2020)
This study aims to describe the influence of learning model on Project Based Learning (PjBL) to the activities and learning outcomes IPS students at SDN 8 Tanantovea. The study population were all students of SDN 8 Tanantovea in the 2018/2019 academic year, a total of 115 people. Sampling was done by purposive sampling technique of grade V SDN 8 Tanantovea as an experimental class used learning model the Project Based Learning (PjBL). The study design used a Pretest-Posttest Design. The statistical test used the t-test. Based on the results of calculations using SPSS, it was obtained that the results of the test of the influence of PPA learning on student learning activities obtained t count value> t table or 0.691> 0.684 so that it can be concluded that there is the influence of PPA learning on the learning activities of grade 5 SDN 8 Tanantovea students. While the learning outcomes obtained value of t count> t table or 0.799> 0.684 so it can be concluded that there is the influence of PjBL learning to the learning outcomes of grade V students of SDN 8 Tanatovea on IPS subjects.